The impact of political stability and macroeconomic variables on foreign direct investment in Turkey - Mohammad, Khudari; Noraina Mazuin, Sapuan; Mohammed Ammeen, Fadhil (2021)
Foreign direct investment (FDI) is one of the most practical types of foreign investment. FDI contributes to job creation, foreign exchange earnings and national income escalation, improving semi-skill and skilled labor. Based on our knowledge, this paper is the first study attempting to investigate the effect of political stability on the FDI in Turkey using an econometric approach. Achieving this objective, a co-integration analysis was conducted between the FDI and its determinants in the short-run and long-run including “macroeconomic indicators” and “Political Stability (PS)” in Turkey. Using annual data from 1974 to 2017 via Auto-Regressive Distributed Lag (ARDL) model. The results confirm the positive correlation between Gross Domestic Product (GDP), openness, domestic savings and political stability and FDI inflows. They also confirm the negative impact of energy consumption, population and inflation on FDI inflows.